Converting Blockchain Into A Strategic Resource - Pooja Jain , Pranjal Jain (International Journal of Advanced Science and Technology, 2020)
Blockchain is being considered as a technological revolution transgressing a massive leap from unauthorized crypto currencies to legit ledger based communication. This paper researches whether blockchain can be deployed as a strategic resource for accessing competitive advantage. This study has innovatively extended the scope of VRIO Test and Resource Based Theory to blockchain technology. The results obtained were remarkable.